DIFFERENTIATING SECONDARY SPEECH DISORDERS DUE TO DELAYED MENTAL DEVELOPMENT FROM SIMILAR CONDITIONS - Rakhmatova Dilnavoz A’zamovna; Jurabayeva Barno Rasulbek qizi (Web of Journals Publishing, 2025)
Secondary speech disorders resulting from delayed mental development (DMD) can resemble various speech and cognitive developmental disorders. This article analyzes the criteria for differentiating speech disorders associated with DMD from conditions such as dyslalia, alalia, dysarthria, aphasia, and general speech underdevelopment. The diagnostic process examines the interrelation between cognitive and speech abilities, as well as the phonetic-phonemic, grammatical, and lexical aspects of a child’s speech. Accurate diagnosis and effective correctional strategies require the use of specialized tests and speech therapy evaluations.
Keywords: Delayed mental development, secondary speech disorders, dyslalia, alalia, dysarthria, aphasia, diagnostics, speech therapy evaluation, phonetics, phonemics, cognition.